CLE19 expressed in the embryo regulates both cotyledon establishment and endosperm development in Arabidopsis - Xu, Ting-Ting (Oxford University Press, 2015)

(untitled) (J Exp Bot)
Embryo and endosperm development are two well co-ordinated developmental processes in seed formation; however, signals involved in embryo and endosperm interactions remain poorly understood. It has been shown before that CLAVATA3/ESR-RELATED 19 (CLE19) peptide is able to trigger root meristem consumption in a CLV2-dependent manner. In this study, the role of CLE19 in Arabidopsis seed development was explored using antagonistic peptide technology. CLE19 is expressed in the epidermal layers of the cotyledon primordia, hypocotyl, and root cap in the embryo. Transgenic plants carrying an antagonistic CLE19 (G6T) construct expressed under the control of CLE19 regulatory elements exhibited a dominant seed abortion phenotype, with defective cotyledon establishment in embryos and delayed nuclear proliferation and cellularization in endosperms. Ectopic expression of CLE19 (G6T) in Arabidopsis under the control of an endosperm-specific ALE1 promoter led to a similar defect in cotyledon establishment in embryos but without an evident effect on endosperm development. We therefore propose that CLE19 may act as a mobile peptide co-ordinating embryo and endosperm development.